Definitions and Explication of the "Social Pediatrics" Concept: Results of the Terminological Analysis - Natalia V. Ustinova ("Paediatrician" Publishers LLC, 2016)
Objective: Our aim was to clarify and standardize the definitions of the term "social pediatrics."Methods: Terminological analysis, functional interpretative content analysis and method of expert assessments.Results: We found 86 definitions of the term "social pediatrics" in the Russian and foreign scientific sources (1939 to 2015). The earliest publication (1945) on social pediatrics was found in the PubMed database. After excluding duplicate and similar definitions, 24 logical definitions were included in the final analysis. Between 1970 and 1979, the highest number of foreign publications related to social pediatrics (PubMed) was found giving the grounds for considering this period the time of the official development of social pediatrics as a branch of science and practice abroad.Discussion: The definitions under the study compose a picture of a broader interpretation of the term "social pediatrics" in Europe, including different children healthcare levels (state, public, individual), while, for example, in Canada, the emphasis shifts towards a purely practical sphere - primary medical care with social pediatrics applied to vulnerable groups of children. Content analysis identified the main categories of social pediatrics in the presented definitions that were recorded in the developed matrix table.Conclusion: Based on the conceptual and categorical apparatus of social pediatrics, including a "holistic approach to healthcare," "social determinants of children's health," "preventive component," "children in difficult circumstances of life," "multidisciplinary approach/interagency cooperation," "system approach (to the organization of healthcare)," "health support," "psychosocial support," and "rights of the child," we introduced our own definition of social pediatrics. Preventive component of social pediatrics is recognized as one of the most important features according to both the content analysis and experts.